The Roles of Human Resource Development in Developing the Whole Person with Disabilities: A Conceptual Model. Issue 4 (10th January 2019) - Lunsford, Dale L.; Dolison, Chiquila N.
Abstract : Persons with disabilities are able to perform many of the same jobs persons without disabilities perform given reasonable accommodations (Burgstahler & Ladner, 2007 ; Freeburg, 1994 ; Hartnett, Stuart, Thurman, Loy, & Batiste, 2011 ). At the same time, persons with disabilities are less likely to have a job (Nafukho, Roessler, & Kacirek, 2010 ). Younger workers especially face this challenge (Nafukho et al., 2010 ). Human resource development researchers have examined factors related to persons with disabilities; however, the research tends to be fragmented. This article presents the results of a literature review to develop a proposed conceptual model for investigating factors associated with human resource development and persons with disabilities in the workplace. This article identifies three attitudinal outcomes and seven factors that may influence these outcomes in this domain.